Response of the thermohaline front and associated submesoscale features in the Korea Strait to wind variation during autumn - Kim, Jong-Kyu; Choi, Byoung-Ju; Lee, Sang-Ho; Son, Young-Tae (Frontiers in Marine Science, 2025)
In the present study, a three-dimensional numerical simulation with a 1 km grid spacing is conducted to investigate the response of the thermohaline front in the northern Korea Strait (KS) and its associated submesoscale features to wind variation. The thermohaline front forms in autumn between the cold Korean Coastal Water near the coast and the Tsushima Warm Current Water offshore in the KS. With northwesterly (down-front) wind, both front and the geostrophic current jet intensify, leading to the development of submesoscale features such as filaments and eddies along the front. To date, there has been no dynamical explanation for the development of these submesoscale features. The numerical simulations in the present study reveal that, during down-front wind events, ageostrophic secondary circulation arises in the upper surface layer due to vertical shear in geostrophic stress, and southwestward ageostrophic currents cross the thermohaline front due to surface wind stress. The divergence of ageostrophic currents actively induces vertical velocities on a horizontal scale below 10 km, enhancing the eddy available potential energy (EAPE) and generating submesoscale features. This study highlights the role of the vertical shear of geostrophic currents in driving the horizontal ageostrophic current in the frontal zone due to frictional processes within the upper layer. Conversely, with northeasterly (up-front) wind, the vertical density structure stabilizes and the front weakens. Simultaneously, ageostrophic secondary circulation diminishes, resulting in a reduction in the EAPE and the submesoscale features. Accompanying submesoscale upwelling and downwelling affects the vertical mixing of nutrients and phytoplankton, which is important for the distribution and survival of coastal organisms.